Hyperdense Pancreatic Ductal Adenocarcinoma: Clinical Characteristics and Proteomic Landscape - Xu, He; Hua, Jie; Meng, Qingcai; Wang, Xiaohong; Xu, Jin; Wang, Wei; Zhang, Bo; Liu, Jiang; Liang, Chen; Yu, Xianjun; Shi, Si (Frontiers in Oncology, 2021)
Purpose: Despite the well-recognized hypodensity of pancreatic ductal adenocarcinoma (PDAC) during contrast-enhanced computed tomography (CECT) examination, a minority of PDAC patients present with hyperdense images. This study was performed to examine the clinical characteristics and protein landscape of PDAC with hyperdensity. Materials and Methods: A total of 844 pathologically confirmed PDAC patients who underwent CECT before surgery were included. During the parenchymal phase of CECT, patients whose tumors presented with higher CT values than the surrounding normal pancreatic parenchyma were assigned to the hyperdense group; all other patients were assigned to the hypodense group. Overall survival (OS) rates were estimated by the Kaplan-Meier method using the log-rank test. Clinical characteristics and CT imaging findings for predicting OS were analyzed by the Cox proportional hazards model. Tumor angiogenesis marker expression was analyzed via immunohistochemistry (IHC) with an anti-CD31 antibody. Proteomics was carried out to compare the possible mechanisms underlying the differential enhancement on CT scans. Results: Based on CECT, 43 PDAC patients had hyperdense lesions, and 801 PDAC patients had hypodense lesions. All 43 patients presented a hyperdense lesion in the parenchymal phase. The mean CECT values of the hyperdense group were higher than those of the hypodense group (102.5 ± 17.4 and 53.7 ± 18.7, respectively, P < 0.001). The hyperdense group had a better prognosis than the hypodense group (median OS, 33.6 vs 20.3 months, P = 0.047). The multivariate analysis showed that age, higher CA19-9 levels (> 300 U/ml), tumor stage, tumor differentiation, tumor CT density, and adjuvant chemotherapy were significant independent prognostic factors. The results of CD31 immunohistochemical staining showed that the hyperdense PDACs had a higher microvessel density than the hypodense group (P < 0.001). A total of 68 differentially expressed proteins were found using the tandem mass tag labeling-based quantification of the proteomes of PDAC tissue samples, and 7 of these proteins (POFUT1, PKP2, P0DOX4, ITPR1, HBG2, IGLC3, SAA2) were related to angiogenesis. Conclusion: Patients who presented with a hyperdense mass on CECT had a higher microvessel density and a better prognosis than those with low-density masses. Anti-angiogenic therapy may be suitable for these patients.